The Use of venous thromboembolism prophylaxis in relatioN to patiEnt risk profilINg (TUNE IN) Wave 3 study - Bassett, J; Schapkaitz, E; Jacobson, B (South African medical journal, 2025)
Background. Thromboprophylaxis significantly reduces the risk of venous thromboembolism (VTE) in hospitalised medical and surgical patients. Nonetheless, the implementation of thromboprophylaxis in South Africa (SA) and worldwide is low.Objective. The TUNE-IN (The Use of venous thromboembolism prophylaxis in relatioN to patiEnt risk profilINg) Wave 3 study is an extension of TUNE-IN Wave 1 and 2. This prospective, cross-sectional study assessed the use of VTE thromboprophylaxis in hospitalised medical, surgical and orthopaedic patients. Methods. Over a 9-month period, 451 consenting patients >18 years of age hospitalised at Charlotte Maxeke Johannesburg Academic Hospital in Gauteng, SA, were systematically included. Patients were assessed and risk stratified according to the IMPROVE (International Medical Prevention Registry on Venous Thromboembolism) bleeding risk and Caprini risk assessment tools. Data on the use of VTE thromboprophylaxis, agent and dose were collected from the hospital records. Results. The study identified 180 (40%) medical, 198 (44%) surgical and 73 (16%) orthopaedic participants. VTE thromboprophylaxis was administered in 263 (58%) study participants. In accordance with the American College of Chest Physicians guidelines on VTE prevention, adequate thromboprophylaxis was administered in 233 (52%). The most common thromboprophylaxis agent was low molecular weight heparin. Subsequently, the Caprini risk assessment tool identified 337 participants (75%) with a VTE risk score >2, whereas the IMPROVE risk assessment tool identified 22 participants (5%) with a high bleeding risk score (≥7). In accordance with the risk assessment tools, recommended thromboprophylaxis was administered in 68% of medical, 59% of surgical and 79% of orthopaedic high-risk participants (p<0.012). The proportion of medical and surgical participants at high VTE risk was similar to that in the Wave 1 and/or 2 studies; however, the rates of VTE thromboprophylaxis in the present study were lower (p=0.097 for medical and p<0.001 for surgical participants). Conclusion. This study shows a significant gap between evidence-based thromboprophylaxis recommendations and clinical practice in a large sample of hospitalised medical, surgical and orthopaedic participants. It is recommended that an institutional VTE risk assessment tool be implemented to standardise risk evaluation and improve the administration of appropriate thromboprophylaxis for hospitalised patients.